Diagnóstico de salud bucodental y factores de riesgo en los centros educativos primarios: Gaspar Gómez de Salazar, Pedro Benavente, Homero Viteri la Fronte y Alfonso María Silva de la Parroquia Gualel del cantón Loja año 2013 - Abad Jiménez, Liliana Alexandra (2013)
Oral diseases, including dental caries, periodontal disease and malocclusion because of their frequency, local discomfort and aesthetic impact on the overall health cause, justifying their attention as a public health problem. Given this, we conducted a study of quantitative, descriptive and prospective, whose aim was to make the diagnosis of oral health and risk factors in primary schools, "Gaspar Gomez de Salazar", "Pedro Benavente", "Homero Viteri the Fronte" and "Alfonso Maria Silva" in the parish of the canton Gualel Loja 2013, examined 86 children, collecting information through dental and medical history survey. The results were: 96.5 % dental caries, gingival inflammation and bleeding 50%, occlusion in deciduous dentition straight terminal plane was 55.6%, in permanent dentition without crowding class I was 41,2%, the risk factors were not brushing 91.8% visit the dentist once a year for 91.8% of consumption of cariogenic food three a day with a 48.8%. The prevalence of certain diseases indicates that the study population pays little attention to oral health care, adhering to ignorance of how to maintain it. Keywords: caries, risk factors, gingival inflammation, malocclusion. Licd. Paola Elizabeth Seraquive Valarezo: traductora.